EVALUATING THE USE OF A NEW BALANCED CRYSTALLOID SOLUTION (STEROFUNDIN) COMPARED TO RINGER’S LACTATE FOR PRIMING CARDIOPULMONARY BYPASS CIRCUITS - SINGH OBEROI, GURPREET; SHARMA, GUNEET; SINGH, MANBIR; RAJWINDER KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aims to evaluate the effects of using either Ringer’s lactate (RL) or a newer balanced crystalloid solution called Sterofundin (SF) as the priming solution for the heart-lung machine during and immediately after single heart valve replacement surgery. Methods: The study included 260 patients bifurcated into groups of SF and RL. A pulsatile roller pump and a membrane oxygenator were used for cardiopulmonary bypass. The circuit was primed either with 500 mL of the balanced 6% hydroxyethyl starch 130/0.4 plus 1000 mL of the RL or 1000 mL of balanced crystalloid solution SF. Results: Significant differences were observed between SF and RL groups based on mean blood pressure, central venous pressure, cardiac index, mixed venous oxygen saturation, blood gas parameters, platelet count, and extubation hours. Conclusion: Stable blood flow is key in heart bypass surgery. Fluid management is complex, and the ideal fluid type is debated. Colloids may help patients with weak hearts. Modern non-colloids are also safe. Research conflicts likely arise from study differences and researcher bias. This study suggests that both fluid types are useful, with colloids potentially better in certain cases. In addition, acetate solutions like SF were found to lower lactate levels. SF also maintains hemostasis, colloid oncotic pressure and reduced blood product requirement. Patient outcomes and intensive care unit stay were similarly affected by priming solutions.